Corn: Its Structure, Polymer, Fiber, Composite, Properties, and Applications - Mohammed A.A.B.A.; Hasan Z.; Omran A.A.B.; Kumar V.; Elfaghi A.M.; Ilyas R.A.; Sapuan S.M. (MDPI, 2023)
Biopolymers; Chemical modification; Composite materials; Crystallinity; Fibers; Grafting (chemical); Military applications; Solvents; Starch; Surface treatment; Biocomposite; Chemical treatments; Composite applications; Corn biocomposite; Corn fiber; Corn starch; Fiber applications; Polymer applications; Polymer fiber composites; Properties improvements; Crosslinking